Association of body mass index and physical activity with fatigue, depression, and anxiety among Iranian patients with multiple sclerosis - Rezaeimanesh, Nasim; Rafiee, Pegah; Saeedi, Roghayyeh; Eskandarieh, Sharareh; Sahraian, Mohammad Ali; Khosravian, Pegah; Abolhasani, Maryam; Razeghi Jahromi, Soodeh; Naser Moghadasi, Abdorreza (Frontiers in Neurology, 2023)
Introduction Depression, fatigue, and anxiety are three common clinical comorbidities of multiple sclerosis (MS). We investigated the role of physical activity (PA) level and body mass index (BMI) as modifiable lifestyle factors in these three comorbidities. Methods A cross-sectional study was conducted in the MS specialist clinic of Sina Hospital, Tehran, Iran. Demographic and clinical data were collected. BMI was categorized in accordance with the WHO’s standard classification. Physical activity (PA) level and sitting time per day were obtained using the short form of the International Physical Activity Questionnaire (IPAQ-SF). Fatigue, anxiety, and depression scores were measured using the Persian version of the Fatigue Severity Scale (FSS), Beck Anxiety Inventory (BAI), and Beck’s Depression Inventory II (BDI-II) questionnaires, respectively. The correlation between the metabolic equivalent of tasks (MET), BMI, and daily sitting hours with depression, anxiety, and fatigue were checked using the linear regression test. The normal BMI group was considered a reference, and the difference in quantitative variables between the reference and the other groups was assessed using an independent sample t-test. Physical activity was classified with tertiles, and the difference in depression, anxiety, and fatigue between the PA groups was evaluated by a one-way ANOVA test. Results In total, 85 MS patients were recruited for the study. The mean ± SD age of the participants was 39.07 ± 8.84 years, and 72.9% (n: 62) of them were female. The fatigue score was directly correlated with BMI (P: 0.03; r: 0.23) and sitting hours per day (P: 0.01; r: 0.26) and indirectly correlated with PA level (P < 0.01; r: −0.33). Higher depression scores were significantly correlated with elevated daily sitting hours (P: 0.01; r: 0.27). However, the correlation between depression with PA and BMI was not meaningful (p > 0.05). Higher anxiety scores were correlated with BMI (P: 0.01; r: 0.27) and lower PA (P: 0.01; r: −0.26). The correlation between anxiety and sitting hours per day was not significant (p > 0.05). Patients in the type I obesity group had significantly higher depression scores than the normal weight group (23.67 ± 2.30 vs. 14.05 ± 9.12; P: 0.001). Fatigue (32.61 ± 14.18 vs. 52.40 ± 12.42; P: <0.01) and anxiety (14.66 ± 9.68 vs. 27.80 ± 15.48; P: 0.01) scores were significantly greater among participants in the type II obesity group in comparison with the normal weight group. Fatigue (P: 0.01) and anxiety (P: 0.03) scores were significantly different in the three levels of PA, but no significant difference was found in the depression score (P: 0.17). Conclusion Our data suggest that a physically active lifestyle and being in the normal weight category are possible factors that lead to lower depression, fatigue, and anxiety in patients with MS.